A contribuição da Khan Academy na aprendizagem de conteúdos matemáticos: uma proposta para alunos com transtorno de déficit de atenção e hiperatividade - TDAH - Russo, Alexandre Matias (2016)
This study, inserted in the search line Information Technology and Mathematics Education, aims to verify the Khan Academy platform's contribution to the learning of Mathematics students diagnosed with Attention Deficit Hyperactivity Disorder - ADHD. To reach that goal, this work is guided by two questions: How extent the Khan Academy platform can contribute to the improvement of Mathematical knowledge of students diagnosed with Attention Deficit Hyperactivity Disorder? Is it possible that the interaction of the student with the Khan Academy platform environment contribute to this improvement? The participants of this research are students enrolled in high school and diagnosed with ADHD. Faced with this research proposal, we present an outline of the history of ADHD since the XIX century, passing through various nomenclatures used up to the present day and the views of experts on this topic. We conducted a literature review on technological interventions for teaching and learning of mathematical content for students with ADHD and Mathematics Education. These researches have contributed to our study and brought relevant aspects of the learning of these students. We present the Khan Academy platform, we check how the Mathematical contents are proposed and available and we choose themes to be worked with the participants. All Mathematics contents were studied in the Khan Academy platform, as well as activities proposed in the paper. We describe the activities of the students in each meeting and their initial analysis of the protocols of the resolutions made and subsequently, the final analysis of the research. We end with the final considerations and conclude with the data presented, that the actions of students diagnosed with ADHD, through the interactions with the platform enable to achieve, understand and improve the subjects studied and contributed to the improvement of the proposed Mathematical knowledge and learning of these schoolchildren